Balanced Urban Development, A Strategy To Address Tension Between Different Contexts (Journal of Planner and Development, 2020)
In their growth stages, cities become an aggregation of different urban contexts as a result of development or investment projects with other goals, which creates urban tension at several levels. Previous studies presented different approaches and methods to address specific aspects of urban stress, and thus contemporary visions and propositions varied, which required a field for research. The research, from a review of the proposals, the research problem emerged in need to study the indicators and trends of balanced urban development that address the tensions between different social, economic and urban contexts". Accordingly, the objective of the research is determined as "Building a comprehensive theoretical framework for indicators of balanced development and their various trends in addressing the manifestations of urban tension". The research hypothesis is that the indicators of balanced development to address urban tension are based on the disparity of forces and the causes and manifestations of tension. The research aims to present this knowledge by adopting the descriptive-analytical method of urban studies to reach the identification of the main themes of balanced urban development and to extract the most important indicators of its achievement. The possibility and formulas of their achievement were measured in the practical study. Three projects were selected that adopted balanced development to address urban tension; the research concluded that the balanced development strategy ensures the activation of the old fabric elements and their interaction with modern features in a manner that ensures the development and preservation of the existing fabric.